On the Trade-off between Power Consumption and Time Synchronization Quality for Moving Targets under Large-Scale Fading Effects in Wireless Sensor Networks - Briff, Pablo (2013)
In this work we find a lower bound on the energy required for synchronizing moving sensor nodes in a Wireless Sensor Network (WSN) affected by large-scale fading, based on clock estimation techniques. The energy required for synchronizing a WSN within a desired estimation error level is specified by both the transmit power and the required number of messages. In this paper we extend our previous work introducing nodes? movement and the average message delay in the total energy, including a comprehensive analysis on how the distance between nodes impacts on the energy and synchronization quality trade- off under large-scale fading effects.